Whole-brain inputs and outputs of Phox2b and GABAergic neurons in the nucleus tractus solitarii - Shao, Liuqi; Kong, Fanrao; Tian, Xiaochen; Deng, Tianjiao; Wang, Yakun; Ji, Yake; Wang, Xiaoyi; Yu, Hongxiao; Yuan, Fang; Fu, Congrui; Wang, Sheng (Frontiers in Neuroscience, 2024)
The nucleus tractus solitarii (NTS) plays a critical role in the homeostatic regulation of respiration, blood pressure, sodium consumption and metabolic processes. Despite their significance, the circuitry mechanisms facilitating these diverse physiological functions remain incompletely understood. In this study, we present a whole-brain mapping of both the afferent and efferent connections of Phox2b-expressing and GABAergic neurons within the NTS. Our findings reveal that these neuronal populations not only receive monosynaptic inputs primarily from the medulla oblongata, pons, midbrain, supra-midbrain and cortical areas, but also mutually project their axons to these same locales. Moreover, intense monosynaptic inputs are received from the central amygdala, the paraventricular nucleus of the hypothalamus, the parasubthalamic nucleus and the intermediate reticular nucleus, along with brainstem nuclei explicitly engaged in respiratory regulation. In contrast, both neuronal groups extensively innervate brainstem nuclei associated with respiratory functions, although their projections to regions above the midbrain are comparatively limited. These anatomical findings provide a foundational platform for delineating an anatomical framework essential for dissecting the specific functional mechanisms of these circuits.